The Role Of Ict In The Development Of Chemical Knowledge Of Future Chemistry Teachers - Sh.Kh. Shomurotova (Genius Publishing Group, 2024)
This article describes a unique approach and methods of pedagogical influence in the development of chemical knowledge of students in chemistry, the means of teaching them to think independently and the factors affecting this, the educational unit in the formation of students as mature pedagogues and is dedicated to the issues of effective use of ICT from scientific research in the educational process.
Keywords: Methods of pedagogical influence; education; research